LITERASI DIGITAL DALAM PENDIDIKAN ISLAM: MENAVIGASI TANTANGAN DAN PELUANG MEDIA SOSIAL UNTUK PEMBELAJARAN AGAMA - Annisa Rahmania Azis; Evi Fatimatur Rusydiyah (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the importance of digital literacy in Islamic education, particularly in addressing the challenges and opportunities presented by social media as a medium for religious learning. Using a Systematic Literature Review (SLR) method based on the PRISMA framework, this article reviews 21 relevant studies published in the last ten years concerning digital literacy and Islamic Religious Education (PAI). The findings reveal that digital literacy in PAI encompasses not only technical skills but also critical thinking, digital ethics, and a deep understanding of Islamic teachings. Although social media offers opportunities for da'wah and interactive learning, it also poses risks such as misinformation, superficial religious understanding, and moral degradation. Therefore, an integrative and collaborative learning strategy is essential, involving teacher training, curriculum reinforcement, and active engagement of families and communities. In conclusion, digital literacy serves as a crucial foundation for shaping a generation of Muslims who are technologically competent, critically minded, and morally upright in the digital era.